1954
DOI: 10.1038/icb.1954.1
|View full text |Cite
|
Sign up to set email alerts
|

THE DETERMINATION OF VITAMIN B12‐ACTIVITY IN THE ORGANS AND EXCRETA OF SHEEP

Abstract: It seems probable from available evidence that vitamin B12 and the closely analogous vitamin Bv2a (or Bi2b) and vitamin Biac all originate in nature only as products of the metabolic activity of certain micro-organisms. The chemical differences between these analogues are minor ones-the cyanogen group, which is attached rather loosely to the cobalt atom in the complex molecule of vitamin B12, is replaced in vitamin Bjoa (or Bjab) by a hydroxyl group, and in vitamin Bi2« by a nitrite radicle; and there is littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1956
1956
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As8ay of vitamin B12. Vitamin B12 activity in liver and blood serum was determined by microbiological assay with Lactobacillus leichmanii (Dawbarn & Hine, 1954; Hine & Smith, 1957).…”
Section: Methodsmentioning
confidence: 99%
“…As8ay of vitamin B12. Vitamin B12 activity in liver and blood serum was determined by microbiological assay with Lactobacillus leichmanii (Dawbarn & Hine, 1954; Hine & Smith, 1957).…”
Section: Methodsmentioning
confidence: 99%
“…A medium low in vitamin B12 was prepared from medium 3 by the method of Davis and Chow (1952), after it was found that all of several preparations of yeast extract available contained about 10-3 ng vitamin B,. activity/mg dry solids, as estimated by the Lactobacillusleichmannii procedure (Dawbarn and Hine 1954). This vitamin B12 activity was probably due to deoxyribonucleosides in the yeast extracts (Smith 1960).…”
Section: (B) Isolation Oj the Organismmentioning
confidence: 99%
“…and Factor B Medium 3 contained sufficient yeast extract to give an apparent vitamin B12 content of 10-6 ng/ml, but this was reduced by the method of Davis and Ohow (1952) to a point where the L. leichmannii assay (Dawbarn and Hine 1954) was insufficiently sensitive to detect any residual vitamin B 12 • An initial inoculum containing 10-6 ng/ml of vitamin B12 activity was serially subcultured seven times at the 1 % level in the vitamin B 12 -low medium. In all these cultures the organism grew normally and reduced heliotrine as rapidly as in the presence of 5 fLg/ml of vitamin B 12 .…”
Section: (D) Growth and Degradation Of Heliotrine In The Pre8ence Andmentioning
confidence: 99%